Analysis effectiveness of online learning during the COVID-19 pandemic - Yudis Ghifari; Diva Aulia Amanda; Angga Hadiapurwa (Curricula: Journal of Curriculum Development, 2022)
The COVID-19 pandemic has forced all countries to implement distance learning and distance restrictions to break the chain of transmission. This article researches the effectiveness of online learning during the Covid-19 pandemic and its impact on student's ability to participate in learning. The research was conducted using a survey method with a quantitative approach. The subjects of this study were active students of the Education Technology study program at the Indonesian Education University class of 2018-2020. The survey data was analyzed by measuring the variables determined using numbers and then analyzed with the applicable statistical procedures. The results showed that online learning was considered less effective because the learning materials were not delivered properly to students. This causes students not to understand the task at hand. Another point that shows the ineffectiveness of online learning is that many issues occur during online learning sessions, for example, internet connection issues, limited interaction, lack of literacy skills, and lack of motivation and productivity of students in its implementation. The level of effectiveness of online learning still can increase if the issues that occur are minimized. Student learning motivation needs to be improved so that the effectiveness of online learning can also increase.   Abstrak Adanya pandemi COVID-19 memaksa seluruh negara untuk melakukan pembelajaran jarak jauh dan harus melakukan pembatasan jarak agar memutus rantai penyebaran. Artikel ini bertujuan untuk meneliti keefektifan pembelajaran daring yang dilakukan pada masa pandemi COVID-19 dan dampaknya terhadap kemampuan siswa dalam mengikuti pembelajaran. Penelitian dilakukan menggunakan metode survei dengan pendekatan kuantitatif. Subjek dari penelitian ini adalah mahasiswa aktif program studi Teknologi Pendidikan Universitas Pendidikan Indonesia angkatan tahun 2018-2020. Analisis data survei yang diperoleh dilakukan dengan cara mengukur variabel yang telah ditentukan menggunakan angka untuk kemudian dianalisis dengan prosedur statistik yang berlaku. Hasil penelitian menunjukkan bahwa pembelajaran daring dinilai kurang efektif karena materi pembelajaran tidak tersampaikan dengan baik terhadap peserta didik. Hal ini menyebabkan peserta didik kurang paham dengan tugas yang dimiliki. Hal lain yang menunjukan ketidak efektifan pembelajaran daring adalah banyaknya hambatan saat pembelajaran daring, misalnya gangguan koneksi, keterbatasan interaksi, kurangnya kemampuan literasi, serta kurangnya motivasi dan produktivitas peserta didik dalam pelaksanaannya. Tingkat keefektifan pembelajaran daring masih memiliki kemungkinan untuk mengalami peningkatan jika kendala yang terjadi dapat diminimalisasi. Motivasi belajar mahasiswa perlu ditingkatkan agar efektivitas pembelajaran daring juga dapat meningkat. Kata Kunci: Efektivitas pembelajaran; pandemi COVID-19; pembelajaran daring